Taxonomic revision of Australian Pristoderus Hope (Coleoptera, Zopheridae) - Turco, Federica; Ślipiński, Adam; Lambkin, Christine L. (Zootaxa, 2012)
Australian species of the genus Pristoderus Hope (Coleoptera, Zopheridae) are revised, with the description of nine newspecies; P. bellus sp. n., P. chloreus sp. n., P. cornutus sp. n., P. duvalensis sp. n., P. monteithi sp. n., P. occidentalis sp.n., P. occultus sp. n., P. spinosus sp. n. and P. tomentosus sp. n., and the re-description of nine species transferred hereinto Pristoderus: P. elongatus comb. n., P. leai comb. n., P. pustulosus comb. n., P. queenslandicus comb. n. (Sparactus),P. productus comb. n., P. repandus comb. n. (Illestus), P. interruptus comb. n. (Ditoma), P. saccharatus comb. n. (Byr-sax), P. zigzag comb. n. (Tarphiomimus) and P. phytophorus comb. n. (Dryptops). A new synonymy is assessed forSparactus proximus Blackburn = Pristoderus interruptus (Erichson) syn. n. Lectotypes are herein designated for Sparac-tus costatus, S. elongatus, S. proximus, S. pustulosus, Illestus grouvellei, I. productus, I. repandus and paralectotypes forSparactus costatus. All Australian species are illustrated with high-resolution photographs and a key to Australian andPapuan species is given. Detailed locality records are given for each species and distribution maps for Australia are provided.